Textbook "Writing Persuasion Text" for Grade VIII Students in Junior High School - Fatmawati, Yeni; Purnomo, Mulyadi Eko; Suhendi, Didi (Jurnal Pendidikan Indonesia, 2022)
This study aims to describe the needs of teachers and students, design a textbook for writing persuasion texts, the results of expert validation and determine the potential effects of textbooks on writing persuasion texts. This research method uses the Jolly and Bolitho and Tesmer development model. The stages of this development are identification of the need for textbooks, exploration of the need for textbooks, realization of contextual textbooks, realization of pedagogical textbooks, producing textbooks, expert validation, revision and field trials. The expert validation assessment obtained results 4.2 from content eligibility, 4.5 from language, 3.4 from presentation and 4.6 from graphics and were declared very valid. The results of the field test through the paired simple test showed the value of writing persuasion text on the theme of education, namely -17.038 significance (2-tailed) of 0.00. The value of writing persuasion text on the health theme is -31.92, a significance (2-tailed) of 0.00. The value of writing persuasion text on the theme of advertising / advertising is -23.385 significance (2-tailed) of 0.00. It is concluded that there is a significant difference between the values before and after using this developed textbook.